In vivo effects of sirolimus and sunitinib of breast cancer prognostic markers - Jaffar, Nurul Fathiyatul Nabila (2020)
Breast cancer is a heterogeneous disease with a wide variety of clinical, pathological, and molecular characteristics, the most commonly diagnosed cancer among females and the leading cause of women cancer death. Hormone receptor studies such as estrogen receptor (ER), progesterone receptor (PgR), and human epidermal growth factor receptor-2 (HER2/neu) are routinely done in prognosis of breast carcinoma and helps in deciding the best treatment. Sirolimus is a natural macrocyclic lactone drug from bacteria with immunosuppressive and anti-proliferative properties by inhibiting mechanistic target of rapamycin (mTOR). Sunitinib is a tyrosine kinase inhibitor (TKI) with antiangiogenic properties. Therefore, it will be interesting to analyse the effect of Sirolimus and Sunitinib in blocking the growth of breast cancer from responding to hormone stimulation. In this study, invasive mammary carcinoma was induced by using 70mg/kg body weight N-Nitroso-N-Methylurea (NMU) in 32 young female Sprague Dawley rats. The gene and protein expressions of ER, PgR and HER2/neu markers were evaluated by using semi-quantitative immunohistochemistry analysis and quantitative real-time PCR assay. Findings from the untreated-control group demonstrated that all mammary lesions are 100% malignant, histopathological characterized with invasive breast carcinoma (IBC) of three major patterns; cribriform, papillary and no special type (NST). Sirolimus treatment showed significant inhibition of mammary tumour progression and downregulate the protein expressions of ER and PgR. However, high expressions of ER and PgR genes expressed on mRNA level might due to Sirolimus cause post-transcriptional regulation in gene. Meanwhile, tumour treated with Sunitinib reduced in diameter after first treatment, but the diameter increased after second treatment, and consequently showed no significant downregulation of ER and PgR. Histologically, Sunitinib treated tumour did not show any aggressive ductal NST histological subtypes. All NMU-induced tumours were HER2/neu-negative scoring. Tumour regression in combination treatment shown was predicted due to Sirolimus predominantly showed anticancer effect rather than Sunitinib. Thus, present findings suggested that Sirolimus is neither synergistic nor additive with Sunitinib.